Violacein antimicrobial activity on Staphylococcus epidermidis and synergistic effect on commercially available antibiotics - Dodou, H.V. (2017)
Aims: The study aimed to assess whether violacein has antimicrobial activity on Staphylococcus epidermidis and synergistically modulates the action of commercially available antimicrobial drugs. Methods and Results: Violacein showed excellent antimicrobial activity on biofilm-forming and nonbiofilm-forming S. epidermidis strains (ATCC 35984) (ATCC 12228), with bacteriostatic (MIC = 20 lg ml 1 and 10 lg ml 1 respectively) and bactericidal effects (MBC = 20 lg ml 1 for both strains), observed in short periods of exposure. The violacein bactericidal concentration led to S. epidermidis death after 2–3 h of exposure. Additionally, violacein synergistically modulated the activity of different antimicrobial classes on S. epidermidis ATCC 12228 (81 8%; n = 9) and on S. epidermidis ATCC 35984 (54 5%; n = 6), reducing the MIC of these antibiotics by up to 16-fold. Conclusion: Violacein shows excellent antimicrobial activity on S. epidermidis strains. Significance and Impact of the Study: Violacein shows the potential for the development of a new drug for the treatment of infections caused by S. epidermidis.